Enhancing the implementation of bilingual education at university through practice: Analysis of CLIL trial lessons by an ESP teacher - Candela Contero Urgal (Master Program in Linguistics, Diponegoro University, 2020)
University teacher training specialised in bilingual education is spreading around Spanish universities. Particularly in Andalusia, where our research originates, universities are searching for systematised methods to train their future bilingual teachers in Content and Language Integrated Learning (CLIL). This paper presents the case of the University of Cadiz, where this study was carried out. This university followed a new training formula led by an ESP (English for Specific Purposes) teacher who performed the role of CLIL teacher trainer. Based on AUTHOR’s (2017) description of the aforesaid CLIL teacher training scheme known as “CLILUT courses” (that is to say, CLIL Training or University Teachers), this study focuses on an in-depth analysis of CLIL trial lesson plans elaborated within such a peer-teacher environment. The present study is then aimed at examining the data obtained through in-class direct observation of 68 CLIL trial lessons which were created from 2010 to 2014 at the University of Cádiz and analysed with the help of rubrics created upon Nunan’s theory (1989). Results show that ESP teachers can offer substantial help for new CLIL university teachers who might face specific foreign language-related problems when starting to take part in bilingual programmes.